Socioeconomic Predictors of Intestinal Parasitic Infections Among Under-Five Children in Rural Dembiya, Northwest Ethiopia: A Community-Based Cross-sectional Study - Zemichael Gizaw; Ayenew Addisu; Mulat Gebrehiwot (SAGE Publishing, 2019)
Background: Soil-transmitted helminths and protozoan parasitic infections are endemic throughout the world. The problem of intestinal parasitic infection is higher among developing countries where children are the most vulnerable groups. Although health information related to parasitic infections is available globally, it is often limited in rural setups in least developed countries. This study was, therefore, conducted to assess socioeconomic predictors of intestinal parasitic infections among under-five children in rural Dembiya, Northwest Ethiopia. Methods: This cross-sectional study was conducted among 224 randomly selected households with under-five children. We used questionnaire to collect data and direct stool examination to identify intestinal parasitic infections. Adjusted odds ratio (AOR) with 95% confidence interval (CI) and P  < .05 was used to identify socioeconomic predictors of parasitic infections. Results: We found that 25.4% (95% CI = [20.2, 31.1]) under-five children had intestinal parasitic infection. Ascaris lumbricoides was the leading infection, which accounted 44 of 224 (19.6%). The prevalence of childhood intestinal parasitic infections was higher among households with no members whose education level is secondary and above (AOR = 3.36, 95% CI = [1.23, 9.17]). Similarly, intestinal parasitic infections were statistically associated with presence of 2 under-five children in a household (AOR = 3.56, 95% CI = [1.29, 9.82]), absence of frequent health supervision (AOR = 3.49, 95% CI = [1.72, 7.09]), larger family size (AOR = 2.30, 95% CI = [1.09, 4.85]), and poor household economic status (AOR = 2.58, 95% CI = [1.23, 5.41]). Conclusions: Significant proportion of children was infected with intestinal parasitic infection in rural Dembiya. Educational status of family members, number of under-five children in a household, health supervision, family size, and wealth index were statistically associated with parasitic infections. Provision of anthelmintic drugs, health supervision, and health education targeted with transmission and prevention of infections are recommended.